Pengaplikasian Soft Skill melalui Kurikulum Akhlak dalam Program Adiwiyata Di SD Alam El-Yamien Tuban - Lindra Nur Khanifah (Al Ulya: Jurnal Pendidikan Islam, 2018)
The application of soft skills we know and we know in the learning process we usually understand into character education. The mission of El-Yamien Tuban Natural Elementary School explained about the development of soft skills for students. In the process of self-development berakhlakul karimah is a part of the moral curriculum that is owned by el-yamien elementary school to apply good character education with habituation and example. Programs in basic education make the surrounding environment as a source of learning also directly related to building character education, especially to instill a loving soul and care for the surrounding environment.